Dependence of substrate binding and catalysis on pH, ionic strength, and temperature for thymine DNA glycosylase: Insights into recognition and processing of G·T mispairs - Maiti, Atanu (2011)
Repair of G·T mismatches arising from deamination of 5-methylcytosine (m(5)C) involves excision of thymine and restoration of a G·C pair via base excision repair (BER). Thymine DNA glycosylase (TDG) is one of two mammalian enzymes that can specifically remove thymine from G·T mispairs. While TDG can excise other bases, it maintains stringent specificity for a CpG context, suggesting deaminated m(5)C is an important biological substrate. Recent studies reveal TDG is essential for embryogenesis; it helps maintain an active chromatin complex and initiates BER to counter aberrant de novo CpG methylation, which may involve excision of actively deaminated m(5)C. The relatively weak G·T activity of TDG has been implicated in the hypermutability of CpG sites, which largely involves C→T transitions arising from m(5)C deamination. Thus, it is important to understand how TDG recognizes and process substrates, particularly G·T mispairs. Here, we extend our detailed studies of TDG by examining the dependence of substrate binding and catalysis on pH, ionic strength, and temperature. Catalytic activity is relatively constant for pH 5.5-9, but falls sharply for pH >9 due to severely weakened substrate binding, and, potentially, ionization of the target base. Substrate binding and catalysis diminish sharply with increasing ionic strength, particularly for G·T substrates, due partly to effects on nucleotide flipping. TDG aggregates rapidly and irreversibly at 37 °C, but can be stabilized by specific and nonspecific DNA. The temperature dependence of catalysis reveals large and unexpected differences for G·U and G·T substrates, where G·T activity exhibits much steeper temperature dependence. The results suggest that reversible nucleotide flipping is much more rapid for G·T substrates, consistent with our previous findings that steric effects limit the active-site lifetime of thymine, which may account for the relatively weak G·T activity. Our findings provide important insight into catalysis by TDG, particularly for mutagenic G·T mispairs.